Dream on - Mlynowski, Sarah (New York : Scholastic Press, 2014)
In this third adventure, Abby, her brother Jonah, and her friend Robin get sucked into the magic mirror and end up in the story of Sleeping Beauty, but when Robin pricks her finger and uses up the sleeping spell, Abby has to come up with a clever solution and a new happily-ever-after.
3.5
3-6
440L
Keywords: Sleeping Beauty (Tale) -- Juvenile fiction; Fairy tales; Magic mirrors -- Juvenile fiction; Brothers and sisters -- Juvenile fiction; Sleeping Beauty (Tale) -- Fiction; Fairy tales; Characters in literature -- Fiction; Magic -- Fiction; Brothers and sisters -- Fiction; Fantasy; Sleeping Beauty (Tale) -- Fiction; Fairy tales; Characters and characteristics in literature -- Fiction; Magic -- Fiction; Siblings -- Fiction; Fantasy fiction; Fairy tales -- Fiction; Characters in literature -- Fiction; Magic -- Fiction; Brothers and sisters -- Fiction; Fairy tales; Fantasy fiction